Perencanaan Produksi Kopi Robusta (Coffea canephora) Menggunakan Metode Logika Fuzzy: Studi Kasus di PT. Perkebunan Nusantara XII Kebun Silosanen - Yuli Wibowo; Rima Malica Mukammila (Politeknik Negeri Jember, 2022)
PT. Perkebunan Nusantara XII Kebun silosanen is one of the state-owned companies in Jember Regency which is engaged in the processing of robusta coffee (green bean). The problem is the mismatch between the company's plan and the seasonally variable market demand, which affects the inventory that must be held, which results in situations like stockouts and overstocks and drives up storage costs. The purpose of this study is to evaluate using two methods, namely fuzzy Tsukamoto and Mamdani. Then determine the best method using mape values and make a company production plan using 3 input variables, namely the amount of demand, inventory and quality realization. The results showed that Tsukamoto's fuzzy method was chosen as an alternative method to be used in the production plan for the next period. The MAPE value obtained is